2017
DOI: 10.3906/tar-1607-60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphuring on physicochemical characteristics andaroma of dried Alkaya apricot: a new Turkish variety

Abstract: IntroductionDrying is one of the oldest preservation techniques for foods and is the most important process in the successful storage of apricots (Göğüş et al., 2007). The objective in drying apricots is to reduce the moisture content to a level that allows safe storage over an extended period. In Turkey, the most common drying method for apricots is open-air sun-drying, requiring low capital, simple equipment, and low energy input (El Halouat and Labuza, 1987;Gezer et al., 2003). Generally, the fruits are spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
3
11
1
1
Order By: Relevance
“…In fact, strong negative correlations between the contents of sucrose with glucose (r = −0.992) and fructose (r = −0.991) content in the samples before storage clearly proved the degradation of sucrose. Consistent with these results, Inserra et al . also reported that the glucose and fructose content increased, whereas the sucrose content decreased in dried apricots (Alkaya variety) after SO 2 treatment.…”
Section: Resultssupporting
confidence: 60%
“…In fact, strong negative correlations between the contents of sucrose with glucose (r = −0.992) and fructose (r = −0.991) content in the samples before storage clearly proved the degradation of sucrose. Consistent with these results, Inserra et al . also reported that the glucose and fructose content increased, whereas the sucrose content decreased in dried apricots (Alkaya variety) after SO 2 treatment.…”
Section: Resultssupporting
confidence: 60%
“…However, the slight increase in melanin concentration (0:0244 ± 0:00001%) can be related to the activity of peroxidase enzyme. Comparable results were reported in white Pacific shrimp, and the results were attributed to the enzymatically produced o-Quinone's and stopping their condensation to melanin through formation of intermediate Quinone called sulfoquinone [39,40]. Figure 5 illustrates IR spectrum of dates' melanin and reference melanin (synthetic melanin, obtained from Sigma).…”
mentioning
confidence: 76%
“…The hue index of dates treated with sulfur dioxide gas increased immediately after the treatment (from 0:703 ± 0:051 to 0:724 ± 0:056) and remained relatively constant during storage. Besides the efficacy of sulfution treatment in inactivation of PPO (complete inactivation, Figure 1) and POD (partial inactivation, Figure 2), the increase in brightness of the yellow color is mainly attributed to conversion of the intermediate o-Quinones to a colorless compounds called sulfoquionons [38,39] and removal of carbonyl chromophores in melanoid structures that led to bleaching effect on the dark pigment [40]. Furthermore, sulfur dioxide is known to be very strong reducing agent; therefore, it also removed hydrogen peroxide which is an important factor in the second browning enzyme peroxidase.…”
Section: Hue Indexmentioning
confidence: 99%
“…For example, Sadeghi et al [22] reported increasing L*, a*, and b* variations for figs and raisins with enhancing microwave powers and timings in the sawtoothed grain beetle (Oryzaephilus surinamensis L.) management. Additionally, Inserra et al [23] observed an increase in L* and b* and a reduction in a* parameters of apricots treated with sulfur before drying.…”
Section: Introductionmentioning
confidence: 95%
“…First, the 3-g samples of the apricot pieces, in five replications and pretreated with CO 2 gas at the concentration of 33.4 mol%, were stirred in 20 mL of distilled water using a magnetic stirrer at 80 • C. After 2 h, the liquid part was separated by filter paper [23]. To determine pH and Brix number, a pH meter and a refractometer were employed, respectively.…”
Section: Determination Of Chemical Propertiesmentioning
confidence: 99%